Pengembangan Teknologi Game Indonesia 3D RPG “The Adventure of Riwut” dengan Unity Engine Berbasis Mobile - Jepli Anuari; Agung Purwanto; Mustaqiem Mustaqiem (Journal of Computer System and Informatics (JoSYC), 2020)
Games have now become an alternative entertainment for various groups. Role Playing Game (RPG) is a game that has elements of a complex story and acting that makes someone feel like a character in the game. This research aims to create a game software in the form of an RPG game using Unity software. The game that is displayed in this final project is based on the folklore of Central Kalimantan entitled "The Adventure Of v Riwut". It is hoped that with this game, folklore can be recognized by the younger generation and preserved. The research method used in making this RPG game is where the research stages are in the form of Requirements Plan, Design Process, and Implementation. The requirements plan stage includes identifying the objectives of the application or system and identifying information needs to achieve those goals. The design process stage includes the design process and makes improvements if there is still a design mismatch between the user and the analyst. The implementation stage, at this stage the programmer develops the design into a program that can be tested. From the results of this research, he succeeded in creating an RPG game entitled "The Adventure Of Riwut" with the collaboration of several figures from other folklore so that the resulting game is not monotonous. With the RPG game "The Adventure Of Riwut", players can get to know one of the folk tales entitled "The Adventure Of Riwut"